2018
DOI: 10.1002/2017je005449
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Structures of Thermal Tides Simulated by a Venus GCM

Abstract: Thermal tides in the Venus atmosphere are investigated by using a GCM named as AFES‐Venus. The three‐dimensional structures of wind and temperature associated with the thermal tides obtained in our model are fully examined and compared with observations. The result shows that the wind and temperature distributions of the thermal tides depend complexly on latitude and altitude in the cloud layer, mainly because they consist of vertically propagating and trapped modes with zonal wave numbers of 1–4, each of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
101
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(120 citation statements)
references
References 74 publications
14
101
1
Order By: Relevance
“…However, the phases of the modeled semidiurnal tides at the cloud level were different in different models, and some model results were different from the LIR result. For example, Takagi et al () showed that the semidiurnal tide has a local temperature maximum of approximately 15 hr at the cloud level in their model, whereas our result suggests the local temperature maxima around 9 and 21 hr. Considering the vertical propagation of the semidiurnal tide, the difference may provide a constraint for the vertical profile of the solar heating in a model, because the wave phase at an altitude should be sensitive to the excitation altitude of the wave that is affected from the solar heating profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the phases of the modeled semidiurnal tides at the cloud level were different in different models, and some model results were different from the LIR result. For example, Takagi et al () showed that the semidiurnal tide has a local temperature maximum of approximately 15 hr at the cloud level in their model, whereas our result suggests the local temperature maxima around 9 and 21 hr. Considering the vertical propagation of the semidiurnal tide, the difference may provide a constraint for the vertical profile of the solar heating in a model, because the wave phase at an altitude should be sensitive to the excitation altitude of the wave that is affected from the solar heating profile.…”
Section: Discussionmentioning
confidence: 99%
“…The terdiurnal tide showed small peaks in the midlatitudes of both hemispheres, which is consistent with a global circulation model (GCM; Takagi et al, ). Whole components showed almost hemispherical symmetry, but the amplitude of the semidiurnal tide in the northern hemisphere was slightly stronger than that in the southern hemisphere.…”
Section: Global Structure Of Thermal Tidesmentioning
confidence: 94%
“…AFES‐Venus has enabled us to reproduce the realistic super rotation under the solar heating based on observations, planetary scale waves (Sugimoto et al, ), a polar vortex surrounded by a cold latitude band called “cold collar” (Ando et al, , ), and planetary scale streak features found in the lower cloud levels (Kashimura et al, ). We also investigated the thermal tides and pointed out that they are important for material transports in the cloud layer (Takagi et al, ). However, Ando et al () showed that the thermal tides reproduced in the AFES‐Venus simulations were not consistent with equatorial thermal structures obtained by radio occultation measurements of Venus Express (VEX) and Akatsuki; namely, the temperature distribution at the cloud levels was shifted by about 30° in the zonal direction.…”
Section: Introductionmentioning
confidence: 90%
“…Once the dark material reaches the midlatitude, the meridional shear of the zonal wind associated with the midlatitude jet stretches the dark feature in the northeast‐southwest (northwest‐southeast) direction in the southern (northern) hemisphere, forming the Y shape. Since the meridional velocity amplitude of the Rossby wave is comparable to the mean meridional velocity, which is estimated to be 1–5 m/s (e.g., Lee, Imamura, et al, ; Lee, Titov, et al, ; Rossow et al, ; Takagi et al, ), the poleward flow undergoes large oscillation, thereby creating the undulation of the boundary between the dark region on the low‐latitude side and the bright region on the high‐latitude side (Figure ). Furthermore, since the velocity of the poleward advection of the dark material is variable depending on the phase relationship between the Kelvin wave and the Rossby wave, the slope of the tilted dark band becomes variable as seen in the mosaic images given by Del Genio and Rossow ().…”
Section: A Scenario For the Formation Of The Y Featurementioning
confidence: 99%